Privacy Shields for Whom? Key Actors and Privacy Discourses on Twitter and in Newspapers. (31st October 2017) - O'Rourke, Cristín; Kerr, Aphra
The sharing of data across borders is core in informational economies. However, the Schrems case against Facebook in 2014 raised important questions about the capacity of existing 'safe harbour' policies and practices of multinational corporations in Europe and North America to protect the privacy of individuals' data. The EU–US 'Privacy Shield' framework was subsequently developed to increase data privacy protections. This paper draws upon a sample of English language newspapers and Twitter accounts in Europe and the US from the summer of 2016 to identify the key actors and discourses surrounding the introduction of the Privacy Shield framework. The findings reveal a dominance of trade, market and security language, a focus on individual informational privacy and the dominance of state and legal actors. We argue that privacy is not being redefined in the context of intercontinental data transfers but rather narrowed to a neoliberal free trade framing of information privacy.